2016
DOI: 10.1111/ans.13498
|View full text |Cite
|
Sign up to set email alerts
|

Admission, management and outcomes of acute pancreatitis in intensive care

Abstract: There have been changes to the admission criteria and management in line with evolving guidelines and, overall, outcomes have improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Higher mortality rates have been observed in Maori populations with cancer 8–10 and inpatient diabetics 11 . There is limited literature regarding outcomes of AP in indigenous populations; however, Maori and indigenous Australians are over‐represented in literature regarding severe pancreatitis 12,13 . Approximately half the population of Northland, New Zealand, live outside a main urban centre and 38% are Maori 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher mortality rates have been observed in Maori populations with cancer 8–10 and inpatient diabetics 11 . There is limited literature regarding outcomes of AP in indigenous populations; however, Maori and indigenous Australians are over‐represented in literature regarding severe pancreatitis 12,13 . Approximately half the population of Northland, New Zealand, live outside a main urban centre and 38% are Maori 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately half the population of Northland, New Zealand, live outside a main urban centre and 38% are Maori 14,15 . A small number of studies have addressed the management and outcomes of AP in New Zealand 12,16–19 . No previous studies have specifically examined differences in presentation and outcomes of rural or Maori patients with AP.…”
Section: Introductionmentioning
confidence: 99%
“…These include the Ranson, [ 19 ] Acute Physiology and Chronic Health Assessment (APACHE) II and III, [ 5 , 20 , 21 ] and Sequential Organ Failure Assessment (SOFA) scoring systems. [ 22 27 ] However, scoring only a single time ignores many factors that can influence the outcome during the course of the illness. The measurements from these scoring systems have been shown to more effectively represent the dynamic changes of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous smaller studies have identified inequities for M aori in NZ requiring critical care for specific presentations, including necrotising fasciitis, 42 acute pancreatitis, 14 trauma 11 and influenza 43 among adults, and Staphylococcus aureus sepsis, 44 pedestrian injuries 45 and severe varicella zoster infection 46 in children.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Previous literature has identified inequity in critical illness admissions for M aori, including trauma, 10,11 stroke 12 and severe infections. 13,14 There is, however, no literature describing M aori health outcomes in a general intensive care unit (ICU) population not specified to a type of presentation.…”
Section: Introductionmentioning
confidence: 99%